Genesis and Spread of Novel Highly Pathogenic Avian Influenza A(H5N1) Clade 2.3.4.4b Virus Genotype EA-2023-DG Reassortant, Western Europe - Van Borm, Steven; Ahrens, Ann Kathrin; Bachofen, Claudia; Banyard, Ashley C.; Bøe, Cathrine Arnason; Briand, François-Xavier; Dirbakova, Zuzana; Engelsma, Marc; Fusaro, Alice; Germeraad, Evelien; Gjerset, Britt; Grasland, Béatrice; et al. (Emerging infectious diseases, 2025)
In Europe, highly pathogenic avian influenza (HPAI) virus circulates in avian wildlife, undergoing frequent reassortment, sporadic introductions in domestic birds, and spillover to mammals. An H5N1 clade 2.3.4.4b reassortant, EA-2023-DG, affecting wild and domestic birds was detected in western Europe in November 2023. Six of its RNA segments came from the EA-2021-AB genotype, but the polymerase basic 2 and polymerase acidic segments originated from low pathogenicity avian influenza viruses. Discrete phylogeographic analyses of concatenated genomes and single polymerase basic 2 and polymerase acidic segments suggested reassortment in summer 2023 near the southwestern Baltic Sea. Subsequent continuous phylogeographic analysis of all concatenated EA-2023-DG genomes highlighted circulation in northwestern Europe until June 2024 and long-distance dispersal toward France, Norway, England, Slovakia, Switzerland, and Austria. Those results illustrate the value of phylodynamic approaches to investigate emergence of novel avian influenza virus variants, trace their subsequent dispersal history, and provide vital clues for informing outbreak prevention and intervention policies.